Magnesium-doped Zinc Oxide as Electron Selective Contact Layers for Efficient Perovskite Solar Cells - Song, Jiaxing; Zheng, Enqiang; Liu, Leijing; Wang, Xiao-Feng; Chen, Gang; Tian, Wenjing; Miyasaka, Tsutomu (ChemSusChem, 2016)
The electron‐selective contact layer (ESL) in organometal halide‐based perovskite solar cells (PSCs) determines not only the power conversion efficiency (PCE) but also the thermostability of PSCs. To improve the thermostability of ZnO‐based PSCs, we developed Mg‐doped ZnO [Zn1−xMgxO (ZMO)] as a high optical transmittance ESL for the methylammonium lead trihalide perovskite absorber [CH3NH3PbI3]. We further investigated the optical and electrical properties of the ESL films with Mg contents of 0–30 mol % and the corresponding devices. We achieved a maximum PCE of 16.5 % with improved thermal stability of CH3NH3PbI3 on ESL with the optimal ZMO (0.4 m) containing 10 mol % Mg. Moreover, this optimized ZMO PSC exhibited significantly improved durability and photostability owing to the improved chemical/photochemical stability of the wider optical bandgap ZMO. Mg+ZnO=improved stability: To improve the power conversion efficiency and the thermostability in ZnO/CH3NH3PbI3‐based perovskite solar cells (PSCs), magnesium‐doped ZnO is developed as the electron‐selective contact layer. The optimized ZMO PSCs exhibit significantly improved durability and photo‐stability.